Inflammatory response to magnesium-based biodegradable implant materials. (1st January 2020) - Costantino, M.D.; Schuster, A.; Helmholz, H.; Meyer-Rachner, A.; Willumeit-Römer, R.; Luthringer-Feyerabend, B.J.C.
Abstract: Biodegradability and mechanical properties of magnesium alloys are attractive for orthopaedic and cardiovascular applications. In order to study their cytotoxicity usually bone cells are used. However, after implantation, diverse and versatile cells are recruited and interact. Among the first ones coming into play are cells of the immune system, which are responsible for the inflammatory reaction. Macrophages play a central role in the inflammatory process due to the production of cytokines involved in the tissue healing but also in the possible failure of the implants. In order to evaluate the in vitro influence of the degradation products of magnesium-based alloys on cytokine release, the extracts of pure magnesium and two magnesium alloys (with gadolinium and silver as alloying elements) were examined in an inflammatory in vitro model. Human promonocytic cells (U937 cells) were differentiated into macrophages and further cultured with magnesium-based extracts for 1 and 3 days (simulating early and late inflammatory reaction phases), either at 37 °C or at 39 °C (mimicking normal and inflammatory conditions, respectively). All extracts exhibit very good cytocompatibility on differentiated macrophages. Results suggest that M1 and even more M2 profiles of macrophage were stimulated by the extracts of Mg. Furthermore, Mg–10Gd and Mg–2Ag extracts introduced a nuancing effect by rather inhibiting macrophage M1 profile. Magnesium-based biomaterials could thus induce a faster inflammation resolution while improving tissue repair. Statement of Significance: Macrophage are the key-cells during inflammation and can influence the fate of tissue healing and implant performance. Magnesium-based implants are biodegradable and bioactive. Here we selected an in vitro system to model early and late inflammation and effect of pyrexia (37 °C versus 39 °C). We showed the beneficial and nuancing effects of magnesium (Mg) and the selected alloying elements (silver (Ag) and gadolinium (Gd)) on the macrophage polarisation. Mg extracts exacerbated simultaneously the macrophage M1 and M2 profiles while Mg–2Ag and Mg–10Gd rather inhibited the M1 differentiation. Furthermore, 39 °C exhibited protective effect by either decreasing cytokine production or promoting anti-inflammatory ones, with or without extracts. Mg-based biomaterials could thus induce a faster inflammation resolution while improving tissue repair. Graphical abstract: Image, graphical abstract